Work in the European Gig Economy: research results from the UK, Sweden, Germany, Austria, The Netherlands, Switzerland and Italy - Huws, Ursula; Spencer, Neil; Syrdal, Dag S.; Holts, Kaire (Brussels, 2017)
"Whether it’s known as the ‘sharing economy’, ‘gig economy’, ‘platform economy’ or ‘crowd work’ there is no disputing the exponential growth of online platforms for managing work across Europe. But surprisingly little is known about the realities of ‘gig work’. Is it a liberating new form of self-employment or a new form of exploitation? How many workers are doing it? Who are they? Is it their main source of income or a top-up to other kinds of work? What is the reality of their working lives? And what are the implications of these new realities for public policy in Europe? This report presents the results of an innovative survey across seven European countries, revealing, for the first time, the extent and characteristics of crowd workers in Austria, Germany, Italy, the Netherlands, Sweden, Switzerland and the UK. The survey results are complemented by in-depth interviews with a range of crowd workers, shedding light on the realities of their working lives, including the stresses, fears and health hazards they face, as well as the satisfactions they experience."